2010
DOI: 10.1007/s00436-010-2095-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of Saccharomyces boulardii or metronidazole in symptomatic children with Blastocystis hominis infection

Abstract: Although many Blastocystis infections remain asymptomatic, recent data suggest it also causes frequent symptoms. Therapy should be limited to patients with persistent symptoms and a complete workup for alternative etiologies. The goal of this study was to compare the natural evolution (no treatment) to the efficacy of Saccharomyces boulardii (S. boulardii) or metronidazole for the duration of diarrhea and the duration of colonization in children with gastrointestinal symptoms and positive stool examination for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 20 publications
1
41
0
1
Order By: Relevance
“…La descripción de fallos terapéuticos y de intolerancia a dosis elevadas de metronidazol ha motivado el empleo de otros fármacos como cotrimoxazol o paromomicina 22 . Algunos autores han encontrado útiles probióticos como el Saccharomyces boulardii 21 .…”
Section: Discussionunclassified
“…La descripción de fallos terapéuticos y de intolerancia a dosis elevadas de metronidazol ha motivado el empleo de otros fármacos como cotrimoxazol o paromomicina 22 . Algunos autores han encontrado útiles probióticos como el Saccharomyces boulardii 21 .…”
Section: Discussionunclassified
“…After reading titles/abstracts, 36 potentially relevant studies were identified. Fourteen studies were excluded after full-text assessment for the following reasons: 3 studies evaluated the preventive effect of probiotic on diarrhea, [25][26][27] 3 studies had no control group, 28-30 2 were evaluated in patients who had persistent diarrhea, 31,32 2 were secondary publication of a study done by Cetina-Sauri et al, 33,34 1 included patients who had Blastocystis hominis infection without diarrhea, 35 1 used a mixed probiotic preparation for intervention, 36 data from 1 study were not reported, 15 and full-text of 1 study was not available. 20 Characteristics of excluded studies are presented in Supplemental Table 2.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…have been previously used for the treatment of diarrhea and enteritis associated with B. hominis as the sole identified pathogen in children and adults (Dunn and Boreham 1991). In a randomized, single blind study, Dinleyici et al (2010) compared no treatment to the efficacy of Saccharomyces boulardii or metronidazole (MTZ) for the duration of diarrhea and the duration of colonization in children with gastrointestinal symptoms and positive stool examination for B. hominis. On day 15, clinical cure was observed in 77.7% in group A (n=18); in 66.6% in group B (n=15); and 40% in group C (n=15) (p<0.031, between groups A and C).…”
Section: Introductionmentioning
confidence: 99%